1997
DOI: 10.1128/jvi.71.10.7372-7380.1997
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus infects mouse and human lymphocytes and induces apoptosis

Abstract: Attenuated and highly neurovirulent rabies virus strains have distinct cellular tropisms. Highly neurovirulent strains such as the challenge virus standard (CVS) are highly neurotropic, whereas the attenuated strain ERA also infects nonneuronal cells. We report that both rabies virus strains infect activated murine lymphocytes and the human lymphoblastoid Jurkat T-cell line in vitro. The lymphocytes are more permissive to the attenuated ERA rabies virus strain than to the CVS strain in both cases. We also repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 45 publications
2
33
1
1
Order By: Relevance
“…Modulation of apoptosis is a common feature of infection by animal viruses and it also contributes to the pathogenesis process [36] . A variety of animal viruses have been identified to induce apoptosis in cultured cells [12,[14][15][16] , which contained adenovirus. Early in 1968, Takemori [37] found that cyt mutants of human adenovirus could provoke more violent CPEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of apoptosis is a common feature of infection by animal viruses and it also contributes to the pathogenesis process [36] . A variety of animal viruses have been identified to induce apoptosis in cultured cells [12,[14][15][16] , which contained adenovirus. Early in 1968, Takemori [37] found that cyt mutants of human adenovirus could provoke more violent CPEs.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is recognized as an important process in different biological systems, including embryonic development, cell turnover, and immune response against tumorigenic or virusinfected cells [6][7][8] . An increasing number of viruses or viral gene products were reported to induce apoptosis both in vitro and in vivo [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…This leads to recruitment and activation of a cascade of proteases and, finally, cell death. Several different viruses, such as the human immunodeficiency virus (HIV), rabies, and hepatitis C virus (HCV), induce the apoptosis of immune cells to dampen or skew the immune response [Thoulouze et al, 1997]. This study was to determine whether during viremia, EV71 infects T cells and induces cell death to evade an immune attack.…”
Section: Introductionmentioning
confidence: 99%
“…Rabies virus, a member of an enveloped RNA virus of the family Rhabdoviridae, that causes a dreadful ancient disease, hydrophobia, is one of the known viruses that can readily induce programmed cell death. The induction of apoptosis by RABV is shown to be dependent on the strain of the virus, the route of inoculation and the type of host cell (30,33,35). RABV-induced apoptosis is mainly found in a particular experimental condition.…”
mentioning
confidence: 99%